Ciborgue: uma concepção do corpo na arte contemporânea - Vares, Manoela Freitas (2013)
This contemporary art study aims to understand how the human body is modified through the contact with technological devices, especially considering Art and Technology works.The concepts of post-human and cyborg are discussed through the art works and so on studied and analyzed in the art field. The hybridization between human body and technology gives to it other features, widening or changing it and transforming it into a cyborg. This concept of cyborg talks about a body that shows new ways of communicating, establishing another power relations and, more importantly, assuming the features of being connectable, upgradeable and public. This master thesis helps the discussion and thinking about artistic experiences that use technologies that provides extensions of the body as an experience in the field of Contemporary Art.